PENGARUH INFORMASI FUNDAMENTAL PADA NILAI INTRINSIK SAHAM DENGAN PENDEKATAN PRICE EARNING RATIO - Wulandari, Ayu; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
Investors do an evaluation and analysis of factors that can affect the intrinsic value of the company's stock price using one of the fundamental analysis methods with Price Earning Ratio (PER) approach. The purpose of this study is to obtain empirical evidence of the influence of firm size, sales growth, capital structure, and dividend policy on intrinsic value of s tock . The population of this study is non-financial companies listed on the Indonesia Stock Exchange period 2012-2015. The number of samples of 16 companies in 4 years of observation obtained 64 total observations by purposive sampling technique. Data analysis used in this research is multiple linear regression analysis. Based on the analysis found that company size, capital structure, and dividend policy had positive effect on the intrinsic value of the stock, while sales growth did not effect on the intrinsic value of the stock . Based on the determination coefficient test, the value of R2 obtained value 0.342 means that the influence of independent variables on dividend policy can be explained by this equation model of 34.2%. While the rest equal to 65.8% influenced by other factors. Keywords:   Firm Size, Sales Growth, Capital Structure, Dividend Policy,Price Earning Ratio .